Kink-band formation in the directionally-solidified Mg/LPSO two-phase alloys - Toko Tokunaga; Koji Hagihara; Michiaki Yamasaki; Tsuyoshi Mayama; Kazuki Yamamoto; Hiroki Narimoto; Taiki Kida; Yoshihito Kawamura; Takayoshi Nakano (Science and Technology of Advanced Materials)
The variation in the mechanical properties with the volume fraction of the long-period stacking ordered (LPSO) phase in directionally solidified (DS) Mg/LPSO two-phase alloys was examined. Unexpectedly, the yield stress of the DS alloys increases non-monotonically with an increase in the volume fraction of the LPSO phase. The LPSO phase is considered an effective strengthening phase in Mg alloys, when the stress is applied parallel to the growth direction. Nevertheless, the highest strength was obtained in alloys with 61–86 vol.% of the LPSO phase, which was considerably higher than that in the LPSO single-phase alloy. It was clarified that this complicated variation in the yield stress was generated from the change in the formation stress of kink bands, which varied with the thickness of the LPSO-phase grains. Furthermore, the coexistence of Mg in the LPSO phase alloy induced the homogeneous formation of kink bands in the alloys, leading to the enhancement of the ‘kink-band strengthening’. The results demonstrated that microstructural control is significantly important in Mg/LPSO two-phase alloys, in which both phases exhibit strong plastic anisotropy, to realize the maximum mechanical properties.